ENT 530 Social Media Portfolio: Nanq G / Muhammad Norman Hakim Alias - Alias, Mohamad Norman Hakim (2021)
Nanq G is a clan name for our teams and members. We established this clan since 2015. This team leader by me (Norman Hakim) who was creative to create something new to raise the name of the clan. We provide a lot of business such as bundle clothing, foodies and dessert, and freelance design and I assigned to manage in foodies and dessert. ‘ Pasti Singgah Lagi’ is a trademark for our business which is My Pizza Batu Pahat. We open up 2 branch of My Pizza Batu Pahat with two different location. The first one was located at Sri Gading , Batu Pahat and the other one, was located at Bukit Perdana, Batu Pahat. The main objective that is to achieve for the business is to offer variety of Pizza to our customer with affordable price and luxurious taste . Our business was started on August in 2020. The best seller every day of our product is Garlic Pizza, followed by Chicken Pizza. According to the customer review, our product gave a fantastic taste because the tangy of the My Pizza make our customer remembered the taste. This product is also liked by many due to the cheap and affordable price. Hence, this product provides a good insight for the continuation of sale to our customers. Since early of its opening, My Pizza Batu Pahat by Nanq G was provide 5 types of pizza, 8 types of sushi and 8 types of donuts with different flavors. Increasing demands for our product results into a good profitable sale revenue to our business project. Therefore, My Pizza Batu Pahat by Nanq G is a good marketable product of choice that can be further expanded to many different areas as the business keeps on growing.